Optimization of the Automated Synthesis of [11C]mHED-Administered and Apparent Molar Activities - Chrysoula Vraka; Verena Pichler; Neydher Berroterán-Infante; Tim Wollenweber; Anna Pillinger; Maximilian Hohensinner; Lukas Fetty; Dietrich Beitzke; Xiang Li; Cecile Philippe; Katharina Pallitsch; Markus Mitterhauser; et al. (MDPI AG, 2019)
The tracer [[11C]meta-Hydroxyephedrine ([[11C]mHED) is one of the most applied PET tracers for cardiac imaging, whose radiosynthesis was already reported in 1990. While not stated in the literature, separation difficulties and an adequate formulation of the product are well known challenges in its production. Furthermore, the precursor (metaraminol) is also a substrate for the norepinephrine transporter, and can therefore affect the image quality. This study aims at optimizing the synthetic process of [[11C]mHED and investigating the effect of the apparent molar activity (sum of mHED and metaraminol) in patients and animals. The main optimization was the improved separation through reverse phase-HPLC by a step gradient and subsequent retention of the product on a weakly-cationic ion exchange cartridge. The µPET/µCT was conducted in ten rats (ischemic model) and the apparent molar activity was correlated to the VOI- and SUV-ratio of the myocardium/intra-ventricular blood pool. Moreover, nine long-term heart transplanted and five Morbus Fabry patients underwent PET and MRI imaging for detection of changes in the sympathetic innervation. In summary, the fully-automated synthesis and optimized purification method of [[11C]mHED is easily applicable and reproducible. Moreover, it was shown that the administered apparent molar activities had a negligible effect on the imaging quality.